140 Mb/s deqpsk modem if stage - Suyabatmaz, M. Akif. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1985., 1985)
Recently, as the digital technology progresses, the exploding capacity of digital information nececities fast digital communication systems. Since the congestion prevailing in many regions of radio frenuency spectrum has created the need for improved spectrum utilization techniques, the demand for multilevel (Mrary) digital modulation techniques has also increased. In this thesis, a differentially encoded and differentially decoded quadrature phase shift keyed modem, employing coherent demodulator, was briefly analy.zed. System building blocks were investigated and the one, proper to high data rate application, was chosen for system realization. A working circuit, was build as an intermediate frequency (IF) stage, operating at 140 Mbit per second, and realized.
Keywords: Digital communications.